2014
DOI: 10.1038/nutd.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short chain fatty acids on the expression of free fatty acid receptor 2 (Ffar2), Ffar3 and early-stage adipogenesis

Abstract: Adipose tissue has a major influence on insulin sensitivity. Stimulation of free fatty acid receptor 2 (FFAR2) has been proposed to influence adipocyte differentiation. We hypothesised that exposing preadipocytes to short chain fatty acids would induce earlier expression of nuclear receptors that co-ordinate adipogenesis, triglyceride accumulation and leptin secretion. 3T3-L1 preadipocytes were differentiated in the presence of 1 μM acetate, 0.1–10 μM propionate or vehicle control. In experiment 1, expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Some studies reported that the SCFAs, propionate and acetate increase the leptin expression in adipocytes in vitro , whereas butyrate has no effects3031. However, Frost et al failed to demonstrate a significant effect of SCFAs on leptin secretion in adipocytes32. Furthermore, the leptin mRNA expression has been found to be up-regulated by GPR43 activation in some studies or by GPR41 activation in others2930.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the SCFAs, propionate and acetate increase the leptin expression in adipocytes in vitro , whereas butyrate has no effects3031. However, Frost et al failed to demonstrate a significant effect of SCFAs on leptin secretion in adipocytes32. Furthermore, the leptin mRNA expression has been found to be up-regulated by GPR43 activation in some studies or by GPR41 activation in others2930.…”
Section: Discussionmentioning
confidence: 99%
“… 43 , 46 Zaibi et al 46 suggest that the SCFA-stimulated increase in leptin expression is mediated by FFA2 and that the downregulation of FFA2 in FFA3 KO mice is responsible for the reduction in SCFA-stimulated leptin secretion observed in FFA3 KO mice. However, Frost et al 47 failed to demonstrate a significant effect of SCFAs on leptin secretion in adipocytes.…”
Section: Methodsmentioning
confidence: 98%
“… 37 , 38 , 42 However, reports investigating the expression of both SCFA receptors in adipose tissue have proven to be inconsistent. 37 , 43 , 45 , 46 , 47 …”
Section: Methodsmentioning
confidence: 99%
“…However, whether these findings extend to human adipocytes, in which both GPR41 and GPR43 are expressed (in contrast to 3T3-L1 adipocytes that only express GPR43) remains to be determined. [126][127][128][129][130] In addition to intracellular (that is, endogenous) lipolysis, extracellular lipolysis mediated by lipoprotein lipase (LPL) might also be affected by SCFA in adipose tissue. Incubation of omental adipose tissue explants from overweight humans with propionate (3 mmol/l for 24 h) resulted in an increased expression of LPL mRNA.…”
Section: Lipolysismentioning
confidence: 99%